2021
DOI: 10.1158/0008-5472.can-20-4125
|View full text |Cite
|
Sign up to set email alerts
|

TIMP1 Triggers Neutrophil Extracellular Trap Formation in Pancreatic Cancer

Abstract: Tumor-derived protein tissue inhibitor of metalloproteinases-1 (TIMP1) correlates with poor prognosis in many cancers, including highly lethal pancreatic ductal adenocarcinoma (PDAC). The noncanonical signaling activity of TIMP1 is emerging as one basis for its contribution to cancer progression. However, TIMP1–triggered progression-related biological processes are largely unknown. Formation of neutrophil extracellular traps (NET) in the tumor microenvironment is known to drive progression of PDAC, but factors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 48 publications
2
46
0
1
Order By: Relevance
“…Tumor-derived protein tissue inhibitor of metalloproteinases-1 (TIMP-1), which correlated with poor prognosis in PDAC, directly triggered the formation of NETs. This effect depended on the interaction of TIMP-1 with its receptor CD63 and subsequent ERK signaling [69]. In addition to tumor cells, CAF-conditioned media can also induce ROS-dependent NETosis by secreting Amyloid β A4 protein.…”
Section: Neutrophil Extracellular Trap In Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-derived protein tissue inhibitor of metalloproteinases-1 (TIMP-1), which correlated with poor prognosis in PDAC, directly triggered the formation of NETs. This effect depended on the interaction of TIMP-1 with its receptor CD63 and subsequent ERK signaling [69]. In addition to tumor cells, CAF-conditioned media can also induce ROS-dependent NETosis by secreting Amyloid β A4 protein.…”
Section: Neutrophil Extracellular Trap In Pdacmentioning
confidence: 99%
“…A recent study showed that plasma NET levels using SYTOX-positive areas could also predict the survival of PDAC patients [69]. High plasma levels of NET markers were indicators of increased death risk of PDAC patients.…”
Section: Prognosis In Pdacmentioning
confidence: 99%
“…Although not conventionally thought to be released by neutrophils themselves, some studies have illustrated that neutrophils do in fact produce SDF-1 at least at the mRNA level [ 127 ]. TIMP-1 is also known to elicit NETosis, particularly in the context of pancreatic cancer [ 128 ]. The production of each cytokine, but lack of increased NETosis, suggests that GBCAs have the ability to influence neutrophil chemoattraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, reports have shown that endogenous G-CSF promotes the progress of several types of cancers, such as neuroblastoma and breast cancer (56,57), and tumor-derived G-CSF plays a critical role in NET formation in breast cancer and lung cancer (39,41,58). Tumor cells can also induce NET formation by secreting a variety of other stimulating factors, such as exosome, transforming growth factor-b (TGF-b), interleukin-1b (IL-1b), extracellular RNA (exRNA), mitochondrial DNA (mtDNA), high mobility group box-1 (HMGB1), cathepsin C (CTSC), tissue inhibitor of metalloproteinases-1 (TIMP-1), CXCL5 (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Formation and Degradation Of Netsmentioning
confidence: 99%
“…Abnormally increased NETs are observed in pancreatic cancer patients and the models of murine orthotopic pancreatic cancer (95,172); these NETs can be regarded as an independent prognostic factor for evaluating the outcomes of patients with PDAC, which are negatively correlated with the OS and recurrence-free survival of patients (40). Existing studies showed that increased levels of NETs in pancreatic cancer are partly due to the direct effect of tumor cells, cancer-associated fibroblasts, or activated platelet (67,76,79,106).…”
Section: Pancreatic Cancermentioning
confidence: 99%